2019
DOI: 10.1021/acsnano.8b09588
|View full text |Cite
|
Sign up to set email alerts
|

Graphene as an Ideal Buffer Layer for the Growth of High-Quality Ultrathin Cr2O3Layers on Ni(111)

Abstract: Metal−oxide nanostructures play a fundamental role in a large number of technological applications, ranging from chemical sensors to data storage devices. As the size of the devices shrinks down to the nanoscale, it is mandatory to obtain sharp and good quality interfaces. Here, it is shown that a two-dimensional material, namely, graphene, can be exploited as an ideal buffer layer to tailor the properties of the interface between a metallic substrate and an ultrathin oxide. This is proven at the interface bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Large-bandgap materials such as hexagonal boron nitride (h-BN) 27 play a critical role in 2D materials, as its inert and ultraflat nature allows it to serve as a substrate for high-mobility 2D devices. Other large-bandgap materials include the transitionmetal oxides (TMO) such as the 2H phase MoO 2 , 1T phase MnO 2 , and, more recently, the octahedral α-MoO 3 , which exhibit hyperbolic optical behavior 28 , the chromium oxide (e.g., Cr 2 O 3 ), known for its multiferroic properties 29 , and mica 30 .…”
Section: Bandgaps In 2d Materials Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Large-bandgap materials such as hexagonal boron nitride (h-BN) 27 play a critical role in 2D materials, as its inert and ultraflat nature allows it to serve as a substrate for high-mobility 2D devices. Other large-bandgap materials include the transitionmetal oxides (TMO) such as the 2H phase MoO 2 , 1T phase MnO 2 , and, more recently, the octahedral α-MoO 3 , which exhibit hyperbolic optical behavior 28 , the chromium oxide (e.g., Cr 2 O 3 ), known for its multiferroic properties 29 , and mica 30 .…”
Section: Bandgaps In 2d Materials Familymentioning
confidence: 99%
“…npj 2D Materials and Applications (2020)29 Published in partnership with FCT NOVA with the support of E-MRS…”
mentioning
confidence: 99%
“…It has been shown that a tiny magnetic moment arises on the carbon atoms, induced by the strong hybridization of graphene π orbitals with Ni or Co 3d states [3,8,11,12]. Furthermore, graphene grown on metals protects highly reactive magnetic surfaces and stabilizes them against oxidation [13][14][15]. Whereas recently a large research effort has been dedicated to investigate Gr-Ni and Gr-Co heterostructures, only a few experimental results for graphene grown on Fe surfaces are available [16][17][18], though iron is the most widespread transition metal, and the technology of passivated Fe films with a graphene membrane can be appealing for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium trioxide (Cr 2 O 3 ), also known as chromium oxide, is used as a functional coating in many fields for its excellent properties such as high hardness, wear resistance, corrosion resistance and low coefficient of friction [1][2][3][4]. Cr 2 O 3 coatings are usually prepared by gas phase deposition.…”
Section: Introductionmentioning
confidence: 99%